Developments in the Law on Imprisonment - Rogan, Mary (My University, 2025)
Over the past fifteen years, the contours of prison law have become much more defined and we now have answers to some fundamental questions about legal liability arising of of prison conditions. To mention just one, it is very welcome that we no longer have a test that a prisoner must prove ‘evil’ or ‘malicious’ intent on the part of the prison authorities when asserting a breach of constitutional rights. This was definitively rejected in the judgment of MacMenamin J in Simpson v. Governor of Mountjoy Prison [2019] and reiterated in McGee v. Governor of Potlaoise Prison [2023]. These cases followed the lead offered by the great judgments in Kinsella v. Governor of Mountjoy Prison and Connlly v Governor of Wheatfield Prison from Hogan J. We also have a warning not to simply repackage Article 3 arguments as constitutional arguments from Simpson, on the relationship between tort principles and constitutional rights, and, sadly, now relatively extensive guidance on the lawful management of situations where a prisoner refuses food or medical treatment (PMD; GDC). As I wrote a couple of years ago, prison law has entered adulthood, a long way from the scant guidance and often informed guess work I had to engage in when in practice in the early and mid 2010s.
PUBLISHED
Keywords: Inclusive Society; Prison Law